Conceptions on genetics in a group of college students - Correia, Patrícia Santana (Springer-Verlag, 2012)
The purpose of this study was to investigate awareness, beliefs, and opinions on genetics in a group of Brazilian college students from several courses. The study used the focus group technique with the participation of 19 students, divided into four groups. Also, it used the isotopic reading technique to analyze the material. The results were divided in four themes: the basic knowledge of genetics, the “new genetics,” including molecular biology and testing, genetic manipulation, and genetics and the media. The participants showed reasonable knowledge on the subject, obtained from various sources, including the printed press, the internet, documentaries, and fictional TV shows. Ethical issues were discussed comprehensively and the groups showed awareness on the hazards brought by genetic reductionism and the need to have some type of regulation regarding genetic manipulation and testing. It is necessary to broaden the debate about the progress in genetics because some of them will affect a significant number of people. This debate should include the lay public, which has been actively participating in decisions involving research and the use of new technologies.